Prevalence of dental caries in pregnant Colombian women and its associated factors - Juliana Velosa-Porras; Nelcy Rodríguez Malagón (BMC, 2023)
Abstract Objective To identify the prevalence of dental caries in pregnant women in the Colombian population and its association with the medical history and social determinants, based on data from the fourth National Oral Health Survey (ENSAB IV). Materials and methods A total of 1,047 pregnant women from different areas of Colombia were evaluated. A dental evaluation was performed using a flat oral mirror and blunt-tipped probe (World Health Organization, 2007). For diagnosis of the dental condition, the DMFT index was used. A negative binomial regression analysis was performed to evaluate the association between social determinants and the DMFT index. Results The results of this national study show a 59% prevalence of caries in this population. Regarding the experience of caries, 89.9% of pregnant women showed having had caries. Conclusions The results of this national study on pregnant women show a high prevalence of dental caries. The women's level of education is an important factor associated with dental caries and filled teeth, so the role of oral health education and dental check-ups are important. Clinical relevance The findings of this study show the oral health situation of pregnant women, with a high prevalence of dental caries. This leads to the development and strengthening of oral health education strategies that empower pregnant women in their care. In addition, dental checkups during pregnancy should be implemented and reinforced to prevent and treat oral pathologies and thus prevent complications during this stage.